Influence of psycho-demographic factors and effectiveness of psycho-behavioural interventions on sexual risk behaviour of in-school adolescents in Ibadan, Nigeria (2012)
Sexual risk behaviours (SRBs) among youths continue to reverse the initial gains in HIV/STD control in Nigeria. Very little is known about the interactive influence of psycho-demographic factors (self concept. HIVIAIDS knowledge, and gendezr) and psycho-behavioural interventions (psycho-education and assertiveness training) in reducing HIV SRBs among at-risk in-school adolescents. The study investigated the influence of psycho-demographic factors and psycho-behavioural interventions on HIV SRB. The quasi-experimental study purposively recruited 120 participants who reported unsafe HTV SRB during a school-wide survey in Ibadan. They responded to an 85-item questionnaire, and were further exposed to a 6-week psycho-behavioura1 treatment. Following a 3x2x2x2 ANCOVA, MCA and descriptive statistics, results showed that treatments significantly influenced HIV SRB (F (2,119) = 11.31, P <0,005). Psycho-education intervention participants recorded greater reductions in HIV SRB (n.40. Ẋ=29.57), followed by the assertiveness training group (n.40. Ẋ=39.68), and lastly the control group (n.40. Ẋ= 43.90). Female adolescents with high self-concept and good knowledge of HIV/AIDS who received psycho-education recorded the greatest reduction in HIV SRB (n6, Ẋ=24.67. SD=5.89). Male adolescents in the control group with low self-concept but with good HIV/AIDS knowledge (n6, Ẋ= 53.50, SD=16.23) recorded the most unsafe post intervention HIV SRB score. Good knowledge of HIVIAIDS alone does not yield safe HIV SRB, but additional exposure to psycho-education, with good self-concept development. Therefore, behavioural techniques should be considered along with-other interventions in STDs and HIV control among in-school adolescents.